Enhanced Electrothermal Analysis for Acetone Gas Detection Based on PolyMUMPs MEMS Sensor - Algamili, Abdullah S. (Institute of Electrical and Electronics Engineers, 2024)
Environmental monitoring for the detection and regulation of toxic gases is of paramount importance. This study proposes the modeling and fabrication of MEMS devices based on the standard Polysilicon Multi-Users MEMS Process (PolyMUMPs) for acetone gas detection. Titanium dioxide ( TiO2 ) nanoparticles has been incorporated onto the top sensor's surface, amplifying its detection sensitivity. The study delves into Electrothermal mechanisms that has integrated with the embedded microheater to induce thermal forces. This enhancement significantly improves the acetone gas detection capabilities of the device with high sensitivity and low detection limit. Results include the displacement amplitude of the uncoated PolyMUMPs sensor, with exploration of the coated device's behavior under different heating voltages. Electrothermal actuation is employed, and the output voltage is measured using an MS3110 universal capacitive readout circuit. Comparisons of uncoated and coated devices has been investigated, demonstrating the influence of the sensing material that improve the detection performance. This investigation delves into the impact of varying coating thickness on the PolyMUMPs sensor's performance. The mass sensitivity of the device is found to be 3.8574 mHz/pg, while the detection limit indicates that the device can detect up to 44 part per billion (ppb) at resonance frequency of 7.627 kHz.